Diagnosis and treatment of 10 cases of idiopathic chondrolysis of the hip. (April 2023) - Guan, Tianan; Zhao, Dun; Xiong, Hao; Fang, Bin; Li, Yue
Objective: To analyze the clinical characteristics, X-ray and magnetic resonance imaging manifestations, and treatment efficacy of idiopathic chondrolysis of the hip. Methods: Ten patients with idiopathic chondrolysis of the hip treated at our hospital from September 2013 to April 2022 were collected, and their clinical features, X-ray and magnetic resonance imaging manifestations, and treatment outcomes were analyzed. Results: Their main clinical features included single hip pain, claudication gait, and pelvic tilt, without specific clinical symptoms and signs. Laboratory tests such as blood analysis, erythrocyte sedimentation rate, C-reactive protein, rheumatoid factor, autoimmune test, coagulation function, interferon release test for tuberculosis infection, and tuberculosis antibody test were normal. In the late stage, the imaging shows degeneration or ankylosis of the joint. The disease progresses rapidly, and joint degeneration can occur in adolescence without effective treatment. Herein, seven patients were treated with recombinant human tumor necrosis factor receptor–antibody type II fusion protein. Among them, four (according to Camarnat magnetic resonance imaging classification, three were Stage I and one was Stage II) showed improved symptoms and function, while two (Stage III) had progressed. One patient (Stage I) who received recombinant human tumor necrosis factor receptor had no significant relief of symptoms, for whom anterior capsular release surgery significantly improved the hip joint motion. Of the four patients who underwent hip release surgery, three showed progression. Conclusion: Idiopathic chondrolysis of the hip has no specific clinical and laboratory tests and a high misdiagnosis rate. Thus, early magnetic resonance imaging is a critical reference for diagnosis. We recommend that patients with magnetic resonance imaging Stage II or earlier be actively treated with recombinant human tumor necrosis factor receptor and start treatment as early as possible. In the third stage, the treatment effect is mediocre, and the narrowed hip space is difficult to change.